What is the Nature of the Dynamics between Government Spending and Aggregate Output in the Nordic Countries? - Marko Senekovič (Naše gospodarstvo/Our economy, 2022)
The main aim of this paper is to examine the relationship between government consumption and aggregate output in five Nordic countries in two different scenarios: first, in periods when government consumption increases and, second, in periods when government consumption decreases. Therefore, the nonlinear ARDL model is applied to test for the presence of a short-run and long-run asymmetry in output response to government consumption. The key findings are as follows. First, based on the linear model, a positive connection between government consumption and economic activity has been confirmed, both in the short and long term, which is also in line with the predictions of economic theory. Second, based on the nonlinear model, six out of ten short- term coefficients are statistically significant, as are six out of ten long-term coefficients, with statistically significant asymmetry detected in four out of ten cases. Thus, estimated test statistics and graphical analysis suggest the presence of a negatively inclined asymmetry in the relationship between government consumption and the dynamic of aggregate output with stronger output response in periods when government consumption decreases.